Intrapericardial immature teratoma with pericardial effusion in a 4-month-old boy - Teizaburo Mori; Kazue Miyake; Yumi Kudo; Takuro Fujita; Mai Kutsukake; Yohei Yamada; Kazunori Tahara; Akihiro Fujino; Ryoichi Kondo; Yukihiro Kaneko; Yuki Saito; Keita Terashima; et al. (Elsevier, 2020)
Intrapericardial teratoma is an extremely rare mediastinal teratoma that arises at the junction of the ascending aorta and right atrial appendage. The teratoma is often complicated by massive pericardial effusion that compresses the heart and lungs, leading to heart failure and/or respiratory distress and potentially fatal outcomes in early infants. A 4-month-old boy was referred to our institute with slowly progressive appetite loss and respiratory distress and was diagnosed with intrapericardial teratoma with pericardial effusion. The patient underwent simultaneous surgical drainage of the pericardial effusion and tumor resection. The tumor was pathologically diagnosed as an immature teratoma. The postoperative course was uneventful. He is now being followed up in the outpatient clinic and shows no clinical or radiological signs of recurrence.